Strength of Bond Covenants and Bond Assessment Framework - Noel Yahanpath; SzeKee Koh (Australasian Accounting, Business and Finance Journal, 2012)
We examine bond covenants of 29 New Zealand bond issues between 2001 and 2007. Results from the study indicate that protection provided for bondholders is weak and limited. On average, only 2-3 types of covenants are embedded with the issues and only 27% of these covenants provide full protection to the bondholders. However, bondholders are not compensated for taking the additional risk. We propose an alternative assessment framework that directly assesses the level of protection offered to bondholders. We calculate the covenant quality score for the issues and classify them into four levels of protection: very high protection, moderate, low and very low. Recent legislative changes will go some way towards improving investor protection and confidence, but the effect is yet to be seen. This proposed scoring framework can be used by potential investors to complement the traditional credit ratings when making their investment decisions.
Keywords: Government policy and regulation; bond covenants; bondholder protection